PENERAPAN PRINSIP TANGGUNG GUGAT DALAM PELAKSANAAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM RANGKA IMPLEMENTASI TRIPLE BOTTOM LINE DI INDONESIA - Misahardi Milamarta (Jurnal Dinamika Hukum, 2012)
The goal of this research is to determine the application of the accountability principle in the implementation of corporate social responsibility within the framework of implementation of triple bottom line in Indonesia. It is a normative legal research using secondary dan primary data. Seconda-ry data obtained through libabry research, while the primary data obtained through in-depth interviews. To ensure the data validity is used the criticism source. Data were analyzed using editing analysis style. The results of this study indicate that the application of an accountability principle is not easy. Standard or criteria that must be applied in case relating to the application of an accountability principle should clearly and objectively. Keywords :  an accountability principle, corporate social responsibility, triple bottom line.